Saving Behavior and Financial Access in the Digital Era: Cross-Country Panel Evidence from High-Income Economies - Muhammad Irfai Sohilauw; Yana Fajriah; Syamsul Alam; Edy Jumady; Hasbiyadi Hasbiyadi (Khazanah Sosial, 2026)
This study aims to address the empirical gap between the expansion of financial access and the persistence of unequal financial behavior in highly digitalized, high-income countries. Specifically, this study analyzes the effects of saving behavior and financial access on both traditional and digital financial behavior, while also examining the moderating role of internet penetration in these relationships. The study employs a quantitative approach using a cross-country panel data design. The data are obtained from the Global Findex surveys conducted in 2014, 2017, and 2021, covering 42 high-income countries with a total of 126 country-year observations. The analysis applies panel data regression to examine the relationships among variables and to test the proposed moderating effects. The results show that saving behavior has a positive and statistically significant effect on both traditional and digital financial behavior, confirming the importance of financial discipline. In contrast, financial access does not exhibit a consistent direct effect. Its influence becomes more relevant in the digital context through interaction with internet penetration, although the moderating effect remains relatively limited. The findings imply that policies should not only focus on expanding financial access but also emphasize strengthening financial capability and digital literacy. In addition, the development of digital financial systems should promote more effective and responsible financial usage. In terms of originality, this study contributes to the literature by simultaneously examining traditional and digital financial behavior within a cross-country empirical framework, while explicitly modeling the moderating role of digital infrastructure, which remains underexplored in previous studies.